Logistic centers as a way of the water transportation logistics development - Shmyhol, Nadiia; Metelenko, Natalia (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The urgency of the research is due to the need to justify the advantages of using water and sea transport in comparison with other modes of transport both in Europe and in Ukraine. Design/methodology/approach The aim of the article is to consider international experience, Ukrainian possibilities of logistic centers creation, and justification of places of their localization for the purpose of development of water transport in Ukraine. The methodological basis of the research is the comprehension of theories and scientific approaches to the logistics of water transport, which are grounded in the works of domestic and foreign scientists. Findings During the study, the following methods and approaches were used: methods of analysis and synthesis, abstract and concrete, historical method, factor analysis, structural and functional analysis, system approach. The analysis of the experience of constructing logistic centers in the leading countries of the world is carried out. Research limitations/implications Taking into account the significant role of transport services in creating logistics centers, they should be created in areas with developed transport infrastructure and can offer intermodal transportation. It is justified to locate logistics centers at the points where the lines of different types of land transport, air and water lines are interspersed, and there is an opportunity to develop a place for the needs of the logistics center, specified conditions for the construction of logistic centers in Ukraine. Originality/value It is proved that today in Ukraine it is expedient to pay attention to the creation of transport and logistics centers in the regions of the country, especially with the developed river and sea infrastructure, to activate the role of the state in the implementation of a number of economic and legislative reforms in support of and development of water transport infrastructure, which will contribute to Ukraine’s involvement in international projects on the development of logistic centers network.